The International Handbook on Innovation - Shavinina, Larisa V. (Oxford Pergamon, 2003)
The International Handbook on Innovation is the most comprehensive and authoritative account available of what innovation is, how it is measured, how it is developed, how it is managed, and how it affects individuals, companies, societies, and the world as a whole. Leading specialists from around the world, responsible for much of the current research in the field, analyze the multidisciplinary and multifaceted nature of innovation, its types and levels, its criteria, its development, its management, its specificity in various domains and contexts, and societal demands on it. They consider innovation from the viewpoints of psychology, management science, business, technology, sociology, philosophy, economics, history, education, art, and public policy.With contributions from over 90 distinguished authors covering 17 nations, readers will obtain expert insight into the latest research and future developments in the field of innovation. The Handbook will present many facets of innovation including its nature, its development, its measurement, its management, and its social, cultural, and historical context. The breadth of this work will allow the reader to acquire a comprehensive and panoramic picture of the nature of innovation within a single handbook. The reader will develop an accurate sense of what spurs potentially creative and innovative people and companies toward their extraordinary achievements and exceptional performances.The handbook can be used as a reference source for those who would like information about a particular topic, or from cover to cover either as a sourcebook or as a textbook in a course dealing with innovation. Anyone interested in knowing the wide range of issues regarding innovation will want to read this handbook.Contributions from over 90 distinguished authors covering 17 nationsInternational in scope, reflecting global perspectivesEssential reading for researchers and practitioners in the fields of psychology, management science, business, technology, sociology, philosophy, economics, history, education art, and public policy
Robert W. Weisberg's chapter "Case Studies of Innovation: Ordinary Thinking, Extraordinary Outcomes" (pp. 204-247) analyzes the development of creative innovation in the careers of Mozart, The Beatles, and Picasso
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Picasso, Pablo -- 1881-1973; The Beatles; Innovation; Creativity; Interdisciplinarity